PENGARUH KEPEMIMPINAN LURAH LEWAJA DALAM MENINGKATKAN KINERJA PARA APARATUR KELURAHAN - Saidang Saidang; Suparman Suparman (Universitas Muhammadiyah Enrekang, 2019)
The Lurah is the leader and coordinator of the administration of government in the work area of ​​the kelurahan which in carrying out its duties receives the delegation of government authority from the Regent / Mayor to handle some of the functions of regional autonomy and the administration of general governmental tasks. As a lurah leader has many roles in his leadership, among others, the role as a catalyst, the role as a facilitator, the role as a problem solver and the role as a communicator.The type of research that I use is research using qualitative methods. In collecting data using data collection methods using Observation, Interview, and Documentation.Based on the results of this study, it was concluded that the Leadership was in charge of organizing Government, Development and Community affairs as well as affairs that were abundant by the Sub-district in accordance with the needs of the kelurahan by taking into account the principles of efficiency and increasing accountability. And in carrying out its administration, the Lurah has the tasks, namely, the implementation of the activities of the Village Administration, Community Empowerment, Community Services, Organizing peace and public order, Maintenance of facilities and public service facilities, Fostering social institutions at the Kelurahan level. In improving the performance of the bureaucracy in Lewaja Village, Enrekang District, Enrekang Regency